Castleman disease mimicking systemic lupus erythematosus: A case report. Issue 38 (September 2018) - Wang, Li; Chen, Hua; Shi, Jing; Tang, Hao; Li, Hang; Zheng, Wenjie; Zhang, Fengchun
Abstract: Rationale: Castleman disease (CD) is a nonclonal lymphoproliferative disorder sometimes manifested systemic inflammatory symptoms. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized with multi-system involvement as well as broad spectrum of serum autoantibodies. When these two conditions happened to have similar clinical spectrum features, the confusion with each other occurred. Patient Concerns: A 46-year-old man suffered from chronic fever, nephrotic syndrome, acute kidney injury, anemia, thrombocytopenia and serositis, as well as hypocomplementemia and negative anti-nuclear antibody. Diagnoses: Meeting the classification criteria for SLE, the patient was diagnosed as SLE at first. The renal biopsy showed that he had endocapillary proliferative glomerulonephritis with negative immunofluorescence. Finally, he was diagnosed with CD after lymph nodes biopsy. Interventions: The patient was treated with oral prednisone (50 mg daily) but got poor response. After being proved to have CD, he was treated with CHOP chemotherapy. Outcomes: His condition was controlled by CHOP chemotherapy. After six course of chemotherapy, the proteinuria disappeared. Lessons: If patients, even qualified by classification criteria of SLE, had negative autoantibody or unsatisfied response to the standard treatment, the original diagnosis should be suspected. The biopsy may be help to identify the final criminals, such as CD.